Citizens, Courts, and Confirmations : Positivity Theory and the Judgments of the American People - Gibson, James L., 1951- (Book collections on Project MUSE., 2009)
In recent years the American public has witnessed several hard-fought battles over nominees to the U.S. Supreme Court. In these heated confirmation fights, candidates' legal and political philosophies have been subject to intense scrutiny and debate. Citizens, Courts, and Confirmations examines one such fight--over the nomination of Samuel Alito--to discover how and why people formed opinions about the nominee, and to determine how the confirmation process shaped perceptions of the Supreme Court's legitimacy. Drawing on a nationally representative survey, James Gibson and Gregory Caldeira use.